Heat Transfer Characteristics and Entropy Generation in Cascaded Air Cavity - Ibrahim, Said M. A.; El-Morshedy, Salah El-Din; Abdelmaksoud, Abdelfatah (International Journal of Engineering and Technology, 2018)
In reality every thermodynamic process is irreversible process. All sort of processes have this kind of macroscopic and microscopic energy loss. Every system in a thermodynamic process, generates finite amount of entropy. The entropy generation is studied for vertical cavity with different configurations. The effect of cavity walls temperature difference, Cavity cascading, and cascading positions on the overall values of entropy generation is reported. An important analogy between this work and thermodynamic analysis of Carnot is observed.